Introducing Hospital Onset Bloodstream Infection (HOBSI) as a Tool to Evaluate Infection Prevention: Assessment of 51 US Hospitals. (4th October 2017) - Fakih, Mohamad; Battjes, Rebecca; Sturm, Lisa; Jones, Lindsey; Groves, Clariecia; Bufalino, Angelo; Hendrich, Ann; Haydar, Ziad
Abstract: Background: Currently, publicly reported infections include a few types of events, and do not provide a comprehensive picture on overall infection prevention practices. Hospital onset bloodstream infection (HOBSI), regardless of source, reflects invasive infection from an at risk patient population in inpatient healthcare settings. Methods: Using one infection prevention surveillance system, we identified all positives blood cultures for 5 organisms commonly associated with healthcare infections ( Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Candida species ) over the 12 months of 2016, across 51 acute care hospitals. Each HOBSI was counted once per patient and was classified based on the NHSN definition. Validation was performed comparing individual site laboratory microbiology data to the surveillance system report. Results: A total of 1, 053 HOBSI events occurred over 2, 797, 568 patient-days at an aggregate rate of 3.76 per 10, 000 patient-days. Small (<100 beds) hospitals had very low event rates. There were significant differences between medium (100–300 beds) size and large (>300 beds) hospitals, specifically candidemia and Gram-negative bacteremia (table). S . A ureus and Candida species represented 57% of all HOBSIs. Facility and system events were trended monthly over time based on individual and all organisms combined and provided an objective assessment of invasive infections over time (figure). Conclusion: Automated reporting of HOBSI for common organisms associated with invasive disease provides an objective method to evaluate infection prevention in medium and large hospitals and potentially benchmarking based on hospital characteristics in the future. Disclosures: All authors: No reported disclosures.